Seasonal variability of nitroaromatic compounds in ambient aerosols: Mass size distribution, possible sources and contribution to water-soluble brown carbon light absorption. (July 2022) - Frka, Sanja; Šala, Martin; Brodnik, Helena; Štefane, Bogdan; Kroflič, Ana; Grgić, Irena
Abstract: Nitroaromatic compounds (NACs) as important constituents of atmospheric humic-like substances (HULIS) and brown carbon (BrC) affect the Earth's climate and pose a serious environmental hazard. We investigated seasonal size-segregated NACs in aerosol samples from the urban background environment in Ljubljana, Slovenia. Total concentrations of twenty NACs in PM15.6 were on average from 0.51 ng m −3 (summer) to 109 ng m −3 (winter), and contributed the most to submicron aerosols (more than 74%). Besides 4-nitrocatechol (4NC) as the prevailing species, methylnitrocatechols (MNCs) and nitrophenols (NPs), we reported on some very rarely mentioned, but also on five novel NACs (i.e., 3H4NBA: 3-hydroxy-4-nitrobenzoic acid, 3MeO4NP: 3-methoxy-4-nitrophenol, 4Et5NC: 4-ethyl-5-nitrocatechol, 3Et5NC: 3-ethyl-5-nitrocatechol and 3MeO5NC: 3-methoxy-5-nitrocatechol). Concentrations of 3MeO5NC, 4Et5NC and 3Et5NC were enhanced during cold seasons, contributing up to 11% to total NAC in winter. In cold season, NAC size distributions were characterized with the peaks in the broader size range of 0.305–1.01 μm (accumulation mode), with 4NC and alkyl-nitrocatechols (∑(M/Et)NC) as the most abundant, followed by 4-nitrosyringol, nitrophenols and nitroguaiacols. In spring, a pronounced peak of ∑(M/Et)NC was observed in the accumulation mode (0.305–0.56 μm) as well as in the coarse one. A strong correlation of all NACs with ∑(M/Et)NC and levoglucosan indicates that primary emissions of wood burning were the most important source of NACs, but their secondary formation (e.g., aqueous-phase at higher ambient RH) in cold season could also be a significant one. In warmer season, NACs may be mostly derived from traffic-related aromatic VOCs. The contribution of NACs to the light absorption of the aqueous extracts was up to 10-times higher (contribution to Abs365 up to 31%) than their mass contributions to WSOC (up to 3%) of corresponding size-segregated aerosols, confirming that most of the identified NACs are strong BrC chromophores. Graphical abstract: Image 1 Highlights: Extensive study on seasonal size-segregated nitroaromatics (NACs) in ambient aerosol. Besides NACs usually reported, five novel NACs unambiguously quantified. Seasonal variability of NACs with the highest contribution to submicron fraction. Wood burning and traffic were the most important sources. NACs contribution to WSOC light absorption up to 10-times higher than to WSOC mass.